2001
DOI: 10.1016/s0272-6386(01)80009-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chemokines and chemokine receptors during human renal transplant rejection

Abstract: • Infiltration of renal allografts by leukocytes is a hallmark of acute transplant rejection. Chemokines attract leukocytes bearing specific chemokine receptors, and the specific leukocyte chemokine receptor phenotype is associated with types of immune responses, ie, T helper subtype 1 (Th1; CXC chemokine receptor 3 [CXCR3], CC chemokine receptor 5 [CCR5]) versus Th2 (CCR3, CCR4, CCR8). We studied the expression of the chemokine monocyte chemoattractant protein-1 and the chemokine receptors CCR2B and CXCR4 mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 31 publications
2
70
0
1
Order By: Relevance
“…In situ hybridization was performed as described previously (21). Slides were deparaffinized in xylene and rehydrated in graded ethanol.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…In situ hybridization was performed as described previously (21). Slides were deparaffinized in xylene and rehydrated in graded ethanol.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…In rejecting murine heart allografts, a pattern of IFN-␥-dependent chemokine induction has been identified that includes induction of IFN-inducible protein 10 (IP-10) (CXCL10) and monokine induced by IFN-␥ (MIG) (CXCL9), which are both ligands of the chemokine receptor CXCR3. Immunohistochemical or cDNA array analysis of human cardiac and kidney transplantation biopsy specimens suggest that the appearance of CXCR3-positive cells, such as activated alloantigen-primed T cells and natural killer cells, strongly correlates to AR (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…There, chemokines and their receptors play an important role in the pathogenesis of acute and chronic glomerular inflammation. Increased expression of the CXCR3 receptor has been demonstrated in patients with inflammatory kidney disease like IgA nephropathy, membranoproliferative glomerulonephritis, rapidly progressive glomerulonephritis, or nephrotoxic nephritis (10,11) and during acute allograft rejection (12).…”
mentioning
confidence: 99%